Characterization of pork meat consumption of the population of Xanxerê, Santa Catarina, Brazil - Kirinus, Jackeline Karsten; Benedetti, Matheus; Pavlik, Willian; Taffarel, Gustavo Vinicius; Belmonte, Camila de Oliveira; Dörr, Andrea Cristina; Téo, Ander Renã (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
The swine stands out in some regions of Brazil and more specifically, in Santa Catarina, mainly by having national leadership in the slaughter of these animals. This study constitutes a very important tool, since the identification of the main consumed cuts and analysis of what it means meat with high quality for the consumer Xanxerense, will identify the user profile and contribute to the production system products meat. Field research with primary data collection using forms applied to pork consumers Xanxerê was used. Of the interviewed, 93.3% reported consuming pork meat. Moreover, it was observed that most of the people receive a personal or family income 2-5 the minimum wage in real. The rib was the main cutting preference. Further, it was found that the clear appearance and visible fa t are features that influence the high degree of quality of pork meat for men and women, respectively. Therefore, it is necessary to invest in actions that demonstrate the socio-economic factors involved in the consumption of pork, as well as studies that analyze the quality of the product and the real environmental impact with its production.